Massive Open Online Course ''Un audace esperimento di apprendimento distribuito'' nelle università - Silari, Fabio (Strumenti per la didattica e la ricerca, 2019)
The so-called 'digital revolution' and the economic and social transformations of the last decades have also involved university education, requiring not only some aspects of traditional lectures to adapt, but also several on-line teaching projects to be launched. A recent aspect of this process, started by North American university institutions such as Stanford, Harvard and the Massachusetts Institute of Technology, is represented by the worldwide offer of Massive Open Online Courses (MOOCs), which have no limit concerning the number of participants. and do not require a binding and expensive registration. Using international literature on the subject, this study analyses the origins and evolution of this new system of university teaching.